Níveis de energia metabolizável e lisina digestível para codornas japonesas após muda forçada - Domiciano, Ivete Ricken (2018)
In the search for improvements in the productive indexes of japanese quails in the laying phase, research is carried out taking into account nutritional factors, such as levels of inclusion of digestible lysine (DL) and metabolizable energy (ME) in the diet. The determination of the adequate levels of these nutrients for egg production of japanese quails after forced molting is of paramount importance, in order to support the nutritional requirements tables, in order to formulate rations of minimum cost and/or maximum economic return, consequently reducing excretion of nitrogen to the environment. However, research on nutritional requirements of japanese quails subjected to forced molting is scanty and controversial. Thus, in chapter 1 a bibliographic review was carried out to present the general picture of quail farming in Brazil, to review the main features of quail and to understand the primordial functions of digestible lysine, metabolizable energy and forced molting for japanese quail. In Chapter 2 an experiment was carried out with the objective of estimating the metabolizable energy and digestible lysine requirements in the diet on the productive performance, internal and external quality of eggs and economic analysis of the diets for japanese quails after forced molting. A total of 216 Japanese quails at 42 weeks of age were used in a completely randomized design in a 3 x 4 factorial scheme (levels of ME = 2.600, 2.875 and 3.150 kcal/kg of feed, and levels of DL = 0,90, 1,05, 1,20 and 1,35%), totaling 12 treatments, with three replicates and six birds per experimental unit. The experimental period lasted 135 days, during which, during the initial 23 days, forced molting was performed by the fasting method and the adaptation to the experimental diets, and in the following 112 days the data of productive performance and egg quality were collected of birds, divided into 4 cycles of 28 days each. The largest egg mass of japanese quails after forced molting was obtained with diets containing 1,09% DL associated with 3.150 kcal/kg ME in the diet. The level of 3.150 kcal/kg of ME in the diet provided the best feed conversion g of feed/g of eggs, kg of feed/dz of eggs produced, higher percentage of posture, specific gravity, percentage and xiii thickness of eggshell of quails. The level of 3.150 kcal/kg of ME associated with 1,35% of DL provided higher egg weight, while the level of 2.875 kcal/kg of ME associated with 1,35% of DL presented the best albumen height and Haugh Unit of eggs, however, with the lowest profitability index of the diets. It was concluded that the nutritional requirement of metabolizable energy for better feed conversion, greater egg mass, percentage of posture, specific gravity and percentage and thickness of eggshell of japanese quails after forced molting is 3.150 kcal/kg of ME. The 1,09% level of digestible lysine in the diet is sufficient to provide greater egg mass, however, for higher egg weight, 1,35% or more of digestible lysine should be used.